DEVELOPING TEACHER SELF-EFFICACY THROUGH PROFESSIONAL LEARNING COMMUNITIES IN SCHOOLS OF REMOTE AREA: A PHENOMENOLOGICAL STUDY - Maria Vatmawaty Bety; Aan Komariah (Nurul Jadid University, 2026)
Teacher professional development in remote areas continues to face challenges due to limited access to resources, professional isolation, and a lack of ongoing support. In this context, Professional Learning Communities (PLCs) are viewed as a collaborative approach with the potential to enhance teacher capacity and self-efficacy. However, empirical evidence regarding the role of PLCs in remote areas remains limited. This study aims to explore teachers' experiences in developing self-efficacy through participation in PLCs in remote schools in East Nusa Tenggara, Indonesia. The study employed a qualitative approach with a descriptive phenomenological design. Data were collected through in-depth semi-structured interviews and document analysis, then analyzed through phenomenological stages. The results indicate that participation in PLCs enhances teacher self-efficacy through collaborative learning, peer support, and reflective practice. This study emphasizes the role of PLCs as a mechanism for teacher empowerment in remote areas and the importance of leadership support, structured collaboration, and resource facilitation for ongoing professional development.